1978
DOI: 10.1254/jjp.28.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enkephalin and Substance P on Sympathetic Nerve Transmission in Mouse Vas Deferens

Abstract: Abstract-Effect of methionine-, leucine-enkephalin (met-,leu-enkephalin) and substance P on the transmission in mouse vas deferens was studied. Both met and leu-enkephalin inhibited electrically induced contraction of vas deferens at 10-8-10-7 M, met-enkephalin being 1.4 times more active than leu-enkephalin.Nalorphine (10-6 M) antagonized these effects. Substance P (10-9-10-7 M) had no effect on the contraction.Metand leu-enkephalin (10-7-10-5 M) decreased the high potassium induced [3H]-nor epinephrine rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Mg may then displace Ca from the X-sites in the potential-dependent calcium channel, decrease the calcium conductance change which accompanies the nerve impulse and therefore block transmitter release. Morphine, as well as the naturally occurring opiates methionine-enkephalin and leucine-enkephalin (Segawa, Murakami, Ogawa & Yajima, 1978), may also block transmitter release by binding to the X-receptors and displacing Ca ions. This would explain the alteration by opiates of Ca binding to phospholipids in the presynaptic membrane (Mule, 1969) as well as their ability to block transmitter release (Dunlap & Fischbach, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Mg may then displace Ca from the X-sites in the potential-dependent calcium channel, decrease the calcium conductance change which accompanies the nerve impulse and therefore block transmitter release. Morphine, as well as the naturally occurring opiates methionine-enkephalin and leucine-enkephalin (Segawa, Murakami, Ogawa & Yajima, 1978), may also block transmitter release by binding to the X-receptors and displacing Ca ions. This would explain the alteration by opiates of Ca binding to phospholipids in the presynaptic membrane (Mule, 1969) as well as their ability to block transmitter release (Dunlap & Fischbach, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case for guinea-pig (Sjostrand and Swedin, 1968;von Euler and Hedqvist, 1974;Zetler and Kampmann, 1979;Growcott et al, 1982;Stjernquist et al, 1983;Rovero et al, 1989;Hall and Morton, 1991a,b;Patacchini et al, 1992;Anthes et al, 2002), mouse (Blackwell et al, 1978;Segawa et al, 1978;Parlani et al, 1995) and rabbit (Stjernquist et al, 1983;Maggi et al, 1992a).…”
Section: Vas Deferensmentioning
confidence: 85%
“…The SP-induced contraction of the guinea pig ileum has been attributed to both a direct action on the smooth muscle and a prejunc tional modulation of acetylcholine release [Hedqvist and von Euler, 1975;Chipkin et al, 1978], although an exclusive action on the smooth muscle has been suggested by Rosell et al [1977], In the case of the mouse vas deferens, conflicting results have been ob tained; on this tissue, the SP myotropic effect is considered to be prejunctional by Segawa et al [1978], or postjunctional by Blackwell et al [1978], Although few studies on postversus prejunctional sites of action of SP on vascular smooth muscle are available, the effects of this peptide on both the rabbit mes-enteric vein [Berube et al, 1978] and the human omental vein [Stjarne, 1980] have been described as postjunctional. The portal vein of the rat has also been shown to be sen sitive to SP [llelle et al, 1980;Hellstrandand Jarhult, 1980], but the mode of action of this peptide on this tissue has not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%